2021
DOI: 10.1002/bit.27840
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of filtration behavior using integrated column chromatography followed by virus filtration

Abstract: We evaluated filtration behavior and virus removal capability for a monoclonal antibodies (mAb) and plasma IgG under constant flow rate directly following flow‐through column chromatography in an integrated process. mAb solution with quantified host cell protein (HCP) content processed in flow‐through mode on in‐series mixed‐mode AEX and modified CEX columns connected to the Planova BioEX filter (pool‐less) achieved HCP logarithmic reduction value (LRV) of 2.3 and 93.9% protein recovery, demonstrating comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 19 publications
4
24
0
Order By: Relevance
“…The total flow-through integrated polishing process has been reported to achieve high mAb purification and robust virus reduction (Shirataki et al, 2021a). In this report, we verify the effectiveness of this integrated process when incorporated into a practical scaled-down end-to-end continuous process.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…The total flow-through integrated polishing process has been reported to achieve high mAb purification and robust virus reduction (Shirataki et al, 2021a). In this report, we verify the effectiveness of this integrated process when incorporated into a practical scaled-down end-to-end continuous process.…”
Section: Introductionmentioning
confidence: 62%
“…Validation of the virus filter incorporated into a continuous process cannot be evaluated individually, unlike in a batch process; rather, it is necessary to consider an appropriate virus validation method for continuous process. Proposals for various inline virus spiking methods adapted for virus validation in a continuous process and confirmation of robust virus removal by these methods has been reported by Lute et al (2011), Bohonak et al (2021, Shirataki et al (2021a) and Malakian et al (2022).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Bohonak et al (2021) used this inline spiking method to evaluate the performance of a continuous virus filtration step, with undetectable levels of XMuLV and MVM using the Viresolve® Pro virus filter operated at a low filtrate flux typical of what might be encountered in continuous bioprocessing. A similar approach was used by Shirataki et al (2021) to evaluate virus clearance for an integrated process consisting of a flow‐through ion exchange chromatography step directly coupled to a Planova™ BioEX virus filter. However, in both studies, the feed was continuously spiked with virus at a uniform level, while the virus clearance was evaluated from the virus titer in pooled samples obtained downstream of the virus filter.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lute et al (2020) showed that both the Planova 20N and BioEX hollow fiber virus removal filters provided very effective virus removal (>4-log clearance under all conditions) over 4 days of continuous operation. In contrast, David, Niklas et al (2019) A similar approach was used by Shirataki et al (2021) to evaluate virus clearance for an integrated process consisting of a flow-through ion exchange chromatography step directly coupled to a Planova™ BioEX virus filter. However, in both studies, the feed was continuously spiked with virus at a uniform level, while the virus clearance was evaluated from the virus titer in pooled samples obtained downstream of the virus filter.…”
mentioning
confidence: 99%